Art Brussels 2002 : 20th contemporary art fair. - Everard, Eric; Gielen, Denis; Art Brussels 2002 (Brussel : Artexis nv. Brussel, 2002)
Aalders, Steven ; Alge, Ingmar ; Allart, Jeroen ; Aubertin, Bernard ; Augustijnen, Sven ; Aupol, Eric ; Bade, David ; Balkenhol, Stephan ; Bart, Cécile ; Basch, Gabriele ; Basilico, Gabriele ; Becher, Bernd & Hilla ; Belin, Valérie ; van Bergen, Thé ; Berkhemer, Madeleine ; Berlanger, Marcel ; Bervoets, Fred ; De Beul, Bert ; Bigert & Bergström ; Bijl, Guillaume ; Biwer, Jean-Marie ; Blake, Jeremy ; Boberg, Oliver ; Brahm, Daniela ; Breuning, Olaf ; Brinkmann, Alke ; De Bruyckere, Berlinde ; Buisman, Sjoerd ; Buylen, Michel ; Casqueiro, Pedro ; Charlton, Alan ; Claerbout, David ; De Cock, Jan ; Cortinovis, Claude ; Crabeels, Cel ; Crépy, Marc ; Damag, Gaston ; Decré, Bruno ; Dederen, Gérald ; Dedobbeleer, Koenraad ; Deleu, Luc ; Delvoye, Wim ; Demmerle, Yannick ; Denicolai, Simona ; Dobai, Sarah ; Doctor Hugo ; Domburg, Bart ; Duprat, Hubert ; Durand, Philippe ; Engelen, William ; Esser, Elger ; Fabre, Jan ; Fänge, Jens ; Fauguet, Richard ; Felten-Massinger ; Fischer, Roland ; Fleury, Sylvie ; Floc'h, Nicolas ; Florschuetz, Thomas ; Fontcuberta, Joan ; Fougeirol, Thomas ; Fragateiro, Fernanda ; Franciscus, Frans ; Freess, Maike ; Freisager, Katrin ; Fries, Pia ; Frydman, Maurice ; Gaillard, Frédéric ; Galliano, Daniele ; Geerinck, Manuel ; Geismar, Jarg ; Gersht, Ori ; Geys, Jef ; Geyskens, Vincent ; Gilbert & George ; Glass, Alan ; Grannan, Katy ; Grosse, Katharina ; Hall, Doug ; Halley, Peter ; Harvey, Guy ; Hemsworth, Gerard ; Hirvimäki, Veikko ; Holland, David ; Holland, Harry ; Horn, Roni ; Houseago, Thomas ; Hubert, Gauthier ; Hutchinson, Peter ; Isaacs, John ; Janssen, Twan ; Janssens, Ann Veronica ; Johannesma, Rob ; Jooris, Tom ; Jordan, Eithne ; Juchtmans, Jus ; Kaoru, Izima ; Kempenaers, Jan ; Kersels, Martin ; Kirwan, Richard ; etc.
Engels
Frans
Nederlands
Art Brussels 2002 : 20th contemporary art fair, Brussels Expo Brussel. Artexis nv. Brussel, 02.05 - 06.05.2002
boek
Keywords: Brussel